Game-based learning in medical education - Xu, Maosen; Luo, Yong; Zhang, Yu; Xia, Ruolan; Qian, Hong; Zou, Xiuhe (Frontiers in Public Health, 2023)
At present, medical education is rapidly evolving. Game-based learning (GBL) has been gradually used for education, and several innovations have emerged. The emergence of serious games and gamification provides alternative approaches for educators to improve the medical teaching process. Both serious games and gamification exert their education-promoting function by providing the possibility of combining learning activities such as feedback, testing, and spaced repetition with active participation and autonomy as well as positive experiences for students. Developing effective GBL modalities has the potential to bring immersive experiences for medical students and improve their study outcomes. Herein, we reviewed recent studies employing GBL in medical education, including serious games and gamification teaching. Furthermore, we also discussed the effectiveness and limitations of GBL to suggest future directions for the development and application of GBL in medical education.